Re-regulating Indonesian Stock Buybacks: Lessons from the United States' Tax Cuts - Alisyahdi, Didik Farkhan; Rahman, Diffaryza Zaki (Yuridika, 2021)
This article compares the corporate income tax cuts enacted by the Indonesian COVID-19 Relief Law and the US Tax Cuts and Jobs Act. Further, it investigates the correlations among the tax cuts in the Tax Cuts and Jobs Act, economic development, and share repurchases in the US and seeks to identify appropriate limitations on share repurchases in Indonesia following the enactment of the COVID-19 Relief Law. This research was carried out using the juridical normative method by tracing the laws and literature concerning share repurchase arrangements in Indonesia and the US. The results show that there is a slight positive correlation between the reduction of corporate income tax and economic development in the US and that the US income tax cuts have caused significant growth in share repurchases. Due to the enactment of the Indonesian COVID-19 Relief Law, which also reduced corporate income taxes, Indonesia may be on the verge of extensive share repurchase activity, as was observed in the US. To tackle this problem, we recommend amending Law No. 40, enacted in 2007 concerning limited liability companies, to re-regulate the restriction on share repurchases.